Correlation between Soluble Transferrin Receptor and Iron Status in Women with Gestational Diabetes - Yousif, Duaa Adil; Esraa M. Kareem; Dhuha S.Mohammed; Hawraa Hussein Khudhayer (Indonesian Journal on Health Science and Medicine, 2025)
Soluble transferrin receptor (sTfR), a cleaved form of transferrin receptor 1 (TfR),serves as a marker of cellular iron demand and is largely unaffected by inflammatory responses. This makes it a potentially reliable indicator of iron status, even in the context of inflammation. Human soluble transferrin receptor (sTfR) concentrations were measured by ELISA in a group of 40 pregnant women with gestational diabetes mellitus (GDM) and a comparison group of 40 pregnant women without GDM. Iron-related parameters were also assessed in both groups using the Cobas Integra 400 Plus systems. Women with GDM exhibited significantly elevated sTfR levels compared to the control group. Ferritin levels were also increased among those with GDM. The results demonstrate elevated sTfR levels in pregnant women with GDM compared to those without the condition. Moreover, a positive association was identified between sTfR ferritin, and hepcidin levels. Elevated ferritin was also positively linked to increased GDM risk Highlights: Pregnant women with gestational diabetes showed significantly higher serum sTfR levels compared to controls. Ferritin levels were markedly elevated in the GDM group, while serum iron and TIBC showed no significant differences. sTfR demonstrated limited diagnostic accuracy for GDM, with only 55% sensitivity and 43% specificity.